Determination of Atenolol in pharmaceutical formulations by continuous flow injection analysis via turbidimetric (T180o) and scattered light effect at two opposite position (2N90o ) using Ayah 4SW-3D-T180 -2N90 -Solar - CFI - Al-Awadie, Nagam; Khudhair, Ahmed (Iraqi Journal of Science, 2023)
A simple, rapid and sensitive method for the analysis of Atenolol in pure and pharmaceutical preparation as an alternative analytical procedure were developed by continuous flow injection analysis via turbidimetric (T180o) and scattered light effect at two opposite position (2N90o). The method is based upon the formation of white precipitate for the ion pair compound by phosphomolybidic acid with Atenolol in aqueous medium. The precipitate is measured via the attenuation of incident light and scattering of the incident light in two opposite direction namely +90o and -90o angle were measured. Chemical and physical parameters were investigated. The linearity of Atenolol is ranged from (0.1-11) mmol.L-1, with correlation coefficient r=0.9938, lower limit of detection (LOD) 0.05 mmol.L-1(3SB)(S/N=3) for n=13 and the relative standard deviation for 7 mmol.L-1 Atenolol solution is lower than 3% (n=7). The method was applied successfully for the determination of atenolol in three pharmaceutical drugs. A comparisons were made between the newly developed method of analysis with the classical method ( uv-spectrophotometry at wave length 274nm) of analysis using the standard addition method via the use of t- test. It shows that there was no significant difference at α=0.05(95% confidence) between the two methods. Therefore the newly developed method can be accepted as an alternative method for the analysis of Atenolol, in addition to comparison between the official value and the calculated value for both methods